Venice alone. The last to stand 1848-1849 - Federico Moro (Nuova Antologia Militare, 2023)
The linkage between the thrust for national unity and recovery of the lost independence represents the specific feature of Venice in the 1848 revolution and explains the stubborn will to fight. The lagoon after all, is the real strategic and geographical centre of gravity of the war in Italy. It would be necessary for the Italians to exploit in an effective way its position and its potential to defeat Austria. To neutralize it is the premise of any counter move of the Empire. Even if slowly, Venice deploys men and means adequate to the challenge, but the inability of the Savoy regime to understand this linkage and to appreciate the maritime dimension of the conflict, responsibility shared by the top ranks of Venice, allows the return of the Empire and its final victory.